Long‐term outcome of a cohort of 272 patients undergoing sialendoscopy. (4th November 2021) - Vanden Daele, Arike; Drubbel, Joekio; Van Lierde, Charlotte; Meulemans, Jeroen; Delaere, Pierre; Vander Poorten, Vincent
Abstract: Objectives: To assess the cohort of patients undergoing sialendoscopic intervention for improvement of symptoms and gland‐related quality of life at long‐term follow‐up. Design: This is a retrospective review of medical records with a prospective follow‐up by questionnaire. Setting & Participants: All patients undergoing sialendoscopy at the University Hospitals Leuven Department of Otorhinolaryngology, Head and Neck Surgery between March 2008 and June 2020. Main outcome measures: The electronic files of the patients were searched for information about their sialendoscopic procedure and follow‐up consultations. We also send the patients a questionnaire by mail to assess symptom control and gland‐related quality of life at long‐term follow‐up. Results: Two hundred seventy‐two sialendoscopies were performed in 221 patients. Median follow‐up time was 37 months. The sialendoscopies were performed in 130 patients for lithiasis, in 66 for stenosis, in 14 for recurrent parotitis of childhood, in 8 for recurrent sialadenitis of unknown origin and in 3 for radioiodine‐induced sialadenitis. Complications occurred in 11 of 272 sialendoscopies (4%). Those were iatrogenic perforations, temporary lingual nerve paresthesia and swelling of the floor of the mouth. 53% of patients returned the questionnaire, for a total of 146 evaluable sialendoscopies. The majority of the responders indicated that sialendoscopy had improved their symptoms (83.6%). Salivary glands could be preserved in 89% of the responder group. The highest percentage of patients reporting residual symptoms was found in the RPC group (81.3%) and the lowest in the lithiasis group (16.2%). Besides age, no statistical differences in demographic and pathological features between the responder and non‐responder groups were found, supporting generalisation of the responders' results to the entire cohort. Conclusions: This study confirms the good long‐term outcomes of sialendoscopic interventions in patients with chronic sialadenitis of different aetiologies and a high rate of gland preservation.